URGENCY OF REGULATION: AIRCRAFT AS OBJECT OF CREDIT GUARANTEE - Annalisa Yahanan; Murzal Murzal; Mada Apriandi; Febrian Febrian (Diponegoro Law Review, 2020)
Until now in Indonesia, there is no specific regulation regarding aircraft as collateral object. As a result, in practice, the aviation industry players experienced obstacles related to aircraft financing by guarantee agreements with aircraft objects. Such conditions create legal uncertainty both for credit providers (creditors) and the aircraft guarantees (debtors), because there are no references or signs that can provide direction in the guarantee agreement. If there is a default by the debtor, the creditor has no legal basis for how to execute it. To fill the legal vacuum, in practice, a guarantee agreement was found with the fiduciary deed of the aircraft. Whereas the Fiduciary Law expressly states that it does not apply to (mortgages) aircraft. While on the other hand, Law No. 20 of 2014 concerning Notary Position gives authority to the notary to make an aircraft mortgage deed. Thus the regulations in Indonesia give signals to use aircraft as collateral object. Such a situation demands the urgency for regulations on aircraft guarantee that can provide legal certainty and legal protection for the parties.